2009
DOI: 10.1093/jxb/ern346
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of storage proteins in developing grain of wheat

Abstract: The processing properties of the wheat flour are largely determined by the structures and interactions of the grain storage proteins (also called gluten proteins) which form a continuous visco-elastic network in dough. Wheat gluten proteins are classically divided into two groups, the monomeric gliadins and the polymeric glutenins, with the latter being further classified into low molecular weight (LMW) and high molecular weight (HMW) subunits. The synthesis, folding and deposition of the gluten proteins take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
133
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(144 citation statements)
references
References 36 publications
(57 reference statements)
10
133
0
1
Order By: Relevance
“…The seed storage protein deposition processes in wheat and rice typically involve: (i) targeting of the nascent polypeptides to the ER lumen; (ii) their folding, followed by assortment and assembly of the appropriate types of polypeptides into protein bodies (PB); and (iii) deposition of the PBs into the endosperm cells by two simultaneous pathways: the standard pathway, via Golgi to the protein storage vacuole (PSV), or accumulation directly into PBs in the ER lumen (Shewry & Halford 2002;Herman & Schmidt 2004;Vitale & Ceriotti 2004;Tosi et al 2009). These complex events, carried out over a period of a few days, clearly indicate the need for 'foldase' catalysts and chaperones.…”
Section: Introductionmentioning
confidence: 99%
“…The seed storage protein deposition processes in wheat and rice typically involve: (i) targeting of the nascent polypeptides to the ER lumen; (ii) their folding, followed by assortment and assembly of the appropriate types of polypeptides into protein bodies (PB); and (iii) deposition of the PBs into the endosperm cells by two simultaneous pathways: the standard pathway, via Golgi to the protein storage vacuole (PSV), or accumulation directly into PBs in the ER lumen (Shewry & Halford 2002;Herman & Schmidt 2004;Vitale & Ceriotti 2004;Tosi et al 2009). These complex events, carried out over a period of a few days, clearly indicate the need for 'foldase' catalysts and chaperones.…”
Section: Introductionmentioning
confidence: 99%
“…However, their proportion decreased rapidly from 10 to 15 DAA, when the synthesis of gluten proteins started, and they accounted for about 20% of total grain proteins at the end of the protein accumulation phase. As according to Tosi et al (2009), synthesis of gluten proteins starts at about 8 DAA, it was expected that grain harvested at 10 DAA would have a very low content of gluten proteins, and their proportion at this stage was about 12-15% of total grain proteins in our study. Both gliadins and glutenins were accumulated rapidly until 35 DAA with gliadins being accumulated faster than glutenins.…”
Section: Discussionmentioning
confidence: 61%
“…Gliadins contribute to the viscosity, while glutenin polymers contribute to the elasticity of wheat dough. Tosi et al (2009) observed gluten protein bodies in developing grain as early as 8 days after anthesis (DAA). Shewry et al (2009) reported that low molecular weight-glutenin subunits (LMW-GS) and gliadins were synthesised and accumulated most rapidly between 12 DAA and 35 DAA, while high molecular weight-glutenin subunits (HMW-GS) accumulated more slowly but for a longer period during grain filling.…”
Section: Introductionmentioning
confidence: 99%
“…The glutenins are typical secretory proteins synthesized in polyribosomes and attached to rough endoplasmic reticulum (ER) in where disulfide bond formation, glutenin protein folding and maturation occur under the help of ER lumenal proteins such as molecular chaperone proteins disulfide isomerase (PDI) and binding protein (BiP) (Bollini and Chrispeels 1979;Shewry 1999;Tosi et al 2009). PDI gene family containing thioredoxin domains is involved in the correct formation of disulphide bond, protein folding and assembling of protein bodies.…”
Section: Discussionmentioning
confidence: 99%